2021
DOI: 10.1007/s12020-021-02807-w
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ACE-2 mRNA by inflammatory cytokines in human thyroid cells: a pilot study

Abstract: Introduction Angiotensin-converting-enzyme-2 (ACE-2) was demonstrated to be the receptor for cellular entry of SARS-CoV-2. ACE-2 mRNA was identified in several human tissues and recently also in thyroid cells in vitro. Purpose Aim of the present study was to investigate the effect of pro-inflammatory cytokines on the ACE-2 mRNA levels in human thyroid cells in primary cultures. Methods Primary thyroid cell cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…SAT is generally secondary to upper respiratory tract infections by several viruses (3,10); thus, SAT might represent a potential complication of SARS-CoV-2 infection. The fact that SARS-CoV-2 recognizes angiotensin-converting enzyme 2 (ACE-2) as its cellular entry receptor (44) and the recent demonstration of ACE-2 expression in follicular thyroid cells would further support this possibility (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…SAT is generally secondary to upper respiratory tract infections by several viruses (3,10); thus, SAT might represent a potential complication of SARS-CoV-2 infection. The fact that SARS-CoV-2 recognizes angiotensin-converting enzyme 2 (ACE-2) as its cellular entry receptor (44) and the recent demonstration of ACE-2 expression in follicular thyroid cells would further support this possibility (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the mRNA of angiotensin-converting enzyme 2 (ACE2) was expressed in thyroid follicular cells. Thus, it was hypothesized that direct entry of the pathogen into the cell may be effective in COVID-19-related SAT cases [12,45,46]. In addition, cross-reactivity, which occurs as a result of the similarity of virus spike proteins encoded in all COVID-19 vaccines, especially mRNA vaccines, with mammalian hexa and heptapeptides (e.g., TPO proteins), seems to be another effective mechanism [39,47].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid damage can be directly related to viral cytotoxicity or an immune response mediated by molecular mimicry [ 4 , 13 , 36 ]. Thyroid exhibits high mRNA expression of ACE2 and TMPRSS2 [ 4 6 ]. In a study examining the reaction of human monoclonal antibodies to SARS-CoV-2 proteins with tissue antigens, high homology between immunogenic epitopes of SARS-CoV-2 to human proteins, including thyroid peroxidase (TPO), was reported [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 uses human angiotensin converting enzyme 2 (ACE2) for cell entry and transmembrane serine protease 2 receptor (TMPRSS2) for S- protein priming [ 2 ]. ACE2 and TMPRSS2 are expressed not only in the upper and lower respiratory tract but also in tissues, like thyroid, exocrine pancreas, intestinal tract, heart, proximal renal tubules, adipocytes, Sertoli and Leydig cells [ 3 6 ]. Possible mechanisms of virus-related injury are direct viral action or indirect damage through inflammatory and immunological pathways.…”
Section: Introductionsmentioning
confidence: 99%